Formulasi dan Uji Mutu Fisik Sediaan Pasta Gigi Herbal Ekstrak Temu Putih (Curcuma zedoaria): Formulation and Physical Quality of Temu Putih Extract (Curcuma zedoaria) as Herbal Toothpaste - Deva Rahayu Nurindah Kusuma Wardani; Cikra Ikhda Nur Hamida Safitri (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Dental caries is one of the oral and dental problems in Indonesia. One of the causes of dental caries is the accumulation of dental plaque which is caused by food scraps that stick to the teeth and undergo fermentation by bacteria. Temu Putih (Curcuma zedoaria) is a native Indonesian plant that contains flavonoids, tannins and saponins that can inhibit bacterial growth. The purpose of this study was to formulate the extract of temu putih (Curcuma zedoaria) into toothpaste and evaluate the physical quality of these preparations. The temu putih extract was obtained by maceration method using 96% ethanol as a solvent. The toothpaste preparation formulation was made with a concentration of extract of temu putih (Curcuma zedoaria) 2%, 4%, 6% with a uniform toothpaste base. Evaluation of toothpaste preparations includes homogeneity, organoleptic, pH, dispersion and foam height tests. The test results of the three toothpaste preparations showed that the three formulations were homogeneous, there was no organoleptic change, the pH range of toothpaste from 6.5 to 8.0 which fulfilled the pH requirements of toothpaste according to SNI 12-3524-1995, namely 4.5 - 10, 5, the spreadability test range is 6.4 - 8.0 cm, and the foam height test range is 6.6 - 8.3 cm.